ECM/ECCM Effects on Voice Transmissions - Buskirk, Ronald L. (International Foundation for Telemetering, 1977)
International Telemetering Conference Proceedings / October 18-20, 1977 / Hyatt House Hotel, Los Angeles, California === An evaluation methodology for conventional and ECCM voice communications is presented, wherein intelligibility of the received message rather than error rate or signal-to-noise ratio is the quantity measured. This allows the engineer to include the psychoacoustic phenomena of a human listener in his system design considerations. Analyses have been performed which allow transformation of speech articulation test results into data more meaningful to the communications engineer. Since message intelligibility is established after baseband reconstruction of the voice signal, this method is universally applicable to most voice transmissions. It is insensitive to the nature of the medium, modulation, and interference sources. Examples are presented showing applications of these guidelines to the design of frequency hopping radios. Tests run on a simulator confirm the analyses. A sample tape is available to demonstrate some of the effects.